Language teaching-learning: Technologies at the center of the paradigmatic confrontation - Miranda , Sérgio Gomes de (Seven Editora, 2023)
This text synthesizes the Research Project: "Language Teaching-Learning: paradigms, ideologies, globalization and technologies", developed in the period 2021-2023. Your Problem: How does the teaching-learning of Language, at the State University of Goiás/Iporá and at the Basic School of Iporá and surrounding municipalities, take place and transform itself in times of remote teaching, mediated by technology, due to the COVID-19 pandemic? A qualitative, ethnographic study. The participants were twelve students of the Literature Course of UEG-Iporá and ten teachers of basic education in Iporá and surrounding areas. Instruments: questionnaire and observation. Analyzed here as a synthesis. DOI:https://doi.org/10.56238/emerrelcovid19-071